(3YUeI GdEfSGf ef dMf GddSGfs - (3GdYKeGfj , eMeO Hf CMeO Hf YKeGf GdYKeGfj GdOjHGLj, hdj GdOjf CHh YHO Gddg,J (B774 (3g` s ((3Ydj Hf eMeO GdefXQGhj s)
(3ChdgG (B:s
(3hHYO, aGdfMh bGfhf JYUe eQGYGJg GdEfSGf ef dMf GddSGf ef QGeg adjYde Cf GdcdeI bhd eaQO s
(3BNQgG (B:s
(3hgj HJQJjH GdMQha(B: (3GdCHPj HdYfHQ, gPjd Je Pdc s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B224 s
Keywords: (3GdfMhs